Environmental interactions between people and birds in semiarid lands of the Zapotitlán Valley, Central Mexico - Yessica Angélica Romero-Bautista; Ana Isabel Moreno-Calles; Fernando Alvarado-Ramos; Maurino Reyes Castillo; Alejandro Casas (BMC, 2020)
Abstract Background Birds have been among the most important element in lives of humans around the world, due to their presence and abundance in practically all ecosystems. Zapotitlán Salinas, a community of the Tehuacán Valley, has been a site of interest for studying ecology of bird communities, but no previous studies addressing the relationship between humans and birds have been conducted in the area. Based on their local knowledge, people of the area shape the use and conservation of local bird fauna diversity, which is being maintained or lost under the influence of factors like commerce, tourism, agriculture intensification or abandonment, public policies for conservation, environmental changes, among others. This study aims to analyze the patterns of interactions between humans and birds in a context of high biocultural diversity with a long history and facing the environmental and social challenges of semiarid areas. Methods Ecological sampling for documenting bird species richness was conducted from November 2015 to May 2017 in three transects that included agroforestry systems, forests, and fallow agricultural land. The method of counting by fixed radius points at 16 points within the study systems was used. Thirty in-depth interviews were conducted with local people who own land in the study areas by random sampling and choosing experts of Zapotitlán Salinas, Puebla, a semiarid natural protected area and, since 2019, recognized as Mixed World Heritage. Some visitor guides of the Helia Bravo Hollis Botanical Garden who are member of the community and local people who dedicated part of their time to catching birds were considered as local experts. They have experience in identifying birds through bird watching and listening to bird songs, as well as their knowledge on behavior and habits of the bird species occurring in their locality. We in addition conducted free listing of bird species recognized by people and interviews on ecological aspects, forms of use, and management of birds using a photographic catalog as visual stimulus. The following aspects were addressed with local people: (i) the bird species of Zapotitlán recognized by them; (ii) the biological, ecological, and behavioral knowledge about these species; (iii) the description of practices of use and management of these animals; (iv) the perceived changes regarding presence and abundance of the wild birds recognized; and (v) the regulations of these practices and uses. Results Through the ecological sampling, we identified 89 bird species, a number representing nearly 68% of all species reported for the Zapotitlán Valley. The species recorded belong to 61 genera, 26 families, and 11 orders. Local people interviewed recognized 62 morphospecies occurring in their territory, and designated them with 50 local names. The interactions of local people with birds and the knowledge related to habitats and habits varied according to people's daily life activities and the ways of inter-generational transmission of knowledge. The interactions identified respond to several motivations. The most intense are those of utilitarian nature (three types of use are recognized: nutritional, medicinal, and ornamental), while other less notorious but equally relevant are those related to the awareness and conservation of biological diversity, and aesthetic appreciation of nature. Also relevant are those interactions shaped by the people's worldview since some species are interpreted as climatic environmental predictors, amulets, or omens. Conclusions To understand the various human-bird environmental interactions, it is necessary not only to address the utilitarian assessment that species have in a specific place but also those associated with cultural expressions and the connection between these aspects. Lifestyles, traditions, and beliefs model intangible forms of use, such as the interpretation of climate predictors. Ancient roles of birds in local culture are ongoing, and new demand of ornamental birds from cities influences catching activities but local and regional regulations have contributed to maintain them below a critical level.